The Effect of Existential Therapy on Divorced Women's Existential Anxiety - Abdollah Aliesmaieli (Journal of Global Pharma Technology, 2017)
The aim of the present study is to investigate the effectiveness of existential therapy on divorced women’s existential anxiety. The study is the result of a quasi-experimental research conducted at Babol Islamic Azad University. The sample size included 22 people assigned to experimental and control groups. To do the study, 22 female university students were selected and after carrying out a pre-test were then randomly assigned to two groups, namely, experimental and control. Then, 12 (at maximum) therapy sessions were held for the experimental group. Finally, both the experimental and control groups were evaluated by a post-test. The data was analyzed by using the covariance test analysis (ANCOVA). The results showed that existential therapy decrease existential anxiety (p<0/01). The post-test scores of existential anxiety for the subjects in the experimental group were significantly lower than the pre-test of the same group and the post-test of the control group. According to the results of the study it is predicted that existential therapy can be used as an effective method for treating the problems of divorcee women. The results of this study were in line with the findings about the treatment of cancer, diabetes and traumatic and post-traumatic stress disorder patients.Keywords: Existential Anxiety, Existential Therapy, Good & Good Test.